Sex Differences in Kidney Transplantation: Austria and the United States, 1978–2018 - Hödlmoser, Sebastian; Gehrig, Teresa; Antlanger, Marlies; Kurnikowski, Amelie; Lewandowski, Michał; Krenn, Simon; Zee, Jarcy; Pecoits-Filho, Roberto; Kramar, Reinhard; Carrero, Juan Jesus; Jager, Kitty J.; Tong, Allison; et al. (Frontiers in Medicine, 2022)
Background Systematic analyses about sex differences in wait-listing and kidney transplantation after dialysis initiation are scarce. We aimed at identifying sex-specific disparities along the path of kidney disease treatment, comparing two countries with distinctive health care systems, the US and Austria, over time. Methods We analysed subjects who initiated dialysis from 1979 to 2018, in observational cohort studies from the US and Austria. We used Cox regression to model male-to-female cause-specific hazard ratios (csHRs, 95% confidence intervals) for transitions along the consecutive states dialysis initiation, wait-listing, kidney transplantation and death, adjusted for age and stratified by country and decade of dialysis initiation. Results Among 3,053,206 US and 36,608 Austrian patients starting dialysis, men had higher chances to enter the wait-list, which however decreased over time (male-to-female csHRs for wait-listing, 1978-1987: US 1.94 [1.71,2.20], AUT 1.61 [1.20,2.17]; 2008-2018: US 1.35 [1.32,1.38], AUT 1.11 [0.94,1.32]). Once wait-listed, the advantage of the men became smaller, but persisted in the US (male-to-female csHR for transplantation after wait-listing, 2008-2018: 1.08 [1.05,1.11]). The greatest disparity between men and women occurred in older age groups in both countries (male-to-female csHR for wait-listing after dialysis, adjusted to 75% age quantile, 2008-2018: US 1.83 [1.74,1.92], AUT 1.48 [1.02,2.13]). Male-to-female csHRs for death were close to one, but higher after transplantation than after dialysis. Conclusions We found evidence for sex disparities in both countries. Historically, men in the US and Austria had 90%, respectively 60% higher chances of being wait-listed for kidney transplantation, although these gaps decreased over time. Efforts should be continued to render kidney transplantation equally accessible for both sexes, especially for older women.